Proinflammatory role of basophils in oxazolone‐induced chronic intestinal inflammation. Issue 9 (3rd August 2022) - Inaba, Kenichi; Higashiyama, Masaaki; Watanabe, Chikako; Tomioka, Akira; Ito, Suguru; Tanemoto, Rina; Mizoguchi, Akinori; Nishii, Shin; Wada, Akinori; Sugihara, Nao; Hanawa, Yoshinori; Horiuchi, Kazuki; et al.
Abstract: Background and Aim: The functions of basophils have not been elucidated until recently because of their rarity. However, with recent developments in basophil‐specific antibodies and basophil‐deficient animals, the roles of basophils in various diseases related to chronic inflammation have been clarified. In this study, we aimed to investigate the roles of basophils in human ulcerative colitis (UC) and oxazolone (OXA) colitis using genetically engineered Mcpt8 DTR mice. Methods: Immunohistochemical staining of human colon specimens was performed to examine the involvement of basophils in the pathogenesis of UC. We examined the correlation between the number of infiltrating basophils and the UC endoscopic index of severity (UCEIS), Mayo score, and Matts score. We also examined the correlation between eosinophil count and basophil infiltration. In murine experiments, we examined whether basophil infiltration was involved in OXA‐induced colitis and whether basophil depletion improved inflammation in Mcpt8 DTR mice. Results: Colonic basophil infiltration was significantly increased in patients with UC. There were significant correlations between UCEIS, Mayo score, Matts score, and the number of infiltrating basophils. In murine OXA‐induced colitis, a significant increase in basophil infiltration was observed. When basophils were depleted by diphtheria toxin in Mcpt8 DTR mice, inflammation improved significantly and mRNA expression of some proinflammatory cytokines, including Tnf‐α and Ifn‐γ decreased significantly. Conclusion: Basophil infiltration correlated with endoscopic, clinical, and pathological scores in human UC independently of eosinophil infiltration, and depletion of basophils ameliorated mucosal inflammation in murine OXA‐induced colitis, collectively suggesting that basophils exert a proinflammatory role in chronic intestinal inflammation such as UC.